ANALISIS BIAYA DAN NILAI TAMBAH PENGOLAHAN WINE MOLASE TEBU DI KARANG ASEM BALI - Farida, Farida (Economic Faculty, Attahiriyah Islamic University, 2019)
This study is aimed to determine how much-added value gained and how much cost needed in processing molasses into wine. The data was used two types of data, primary and secondary. The primary gained from direct observation and interview, while the secondary gained from related literature and agencies. We used a descriptive data processing method. Collected data and information then analyzed qualitatively and quantitatively. Quantitative data used to analyzed cost and added value. In the processing of molasses into wine, the results show got Rp262.500.000,- turnover and Rp96.325.000,- total production cost so that we gained Rp166.175.000,- profit income with 2,73 R/C score. This result makes it economically profitable and worth to be done. The added value gained from each liter of molasses processed into wine is Rp.87.350-, also interpreted as 31,20% added value ratio. Keywords: wine, sugar cane molasses, added value, cost analysis